2006
DOI: 10.1101/gad.1390506
|View full text |Cite
|
Sign up to set email alerts
|

The novel SAM domain protein Aveugle is required for Raf activation in the Drosophila EGF receptor signaling pathway

Abstract: Activation of the Raf kinase by GTP-bound Ras is a poorly understood step in receptor tyrosine kinase signaling pathways. One such pathway, the epidermal growth factor receptor (EGFR) pathway, is critical for cell differentiation, survival, and cell cycle regulation in many systems, including the Drosophila eye. We have identified a mutation in a novel gene, aveugle, based on its requirement for normal photoreceptor differentiation. The phenotypes of aveugle mutant cells in the eye and wing imaginal discs rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 68 publications
1
26
0
Order By: Relevance
“…Functional characterization of HYP/AVE (referred to as HYP thereafter) indicated that it acts downstream of RAS, but at a step upstream of RAF. Furthermore, analysis of loss-offunction mutations confirmed its role downstream of EGFR during eye and wing development (Roignant et al, 2006). HYP presumably functions downstream of other RTKs as it has recently been identified in a cell-based genome-wide RNAi screen for genes required for ERK activation induced by various RTKs, including the Insulin receptor and a homolog of the plateletderived growth factor/vascular endothelial growth factor receptor (Friedman and Perrimon, 2006).…”
Section: Cnk Proteins Are Multidomain-containing Scaffoldsmentioning
confidence: 93%
See 2 more Smart Citations
“…Functional characterization of HYP/AVE (referred to as HYP thereafter) indicated that it acts downstream of RAS, but at a step upstream of RAF. Furthermore, analysis of loss-offunction mutations confirmed its role downstream of EGFR during eye and wing development (Roignant et al, 2006). HYP presumably functions downstream of other RTKs as it has recently been identified in a cell-based genome-wide RNAi screen for genes required for ERK activation induced by various RTKs, including the Insulin receptor and a homolog of the plateletderived growth factor/vascular endothelial growth factor receptor (Friedman and Perrimon, 2006).…”
Section: Cnk Proteins Are Multidomain-containing Scaffoldsmentioning
confidence: 93%
“…HYP presumably functions downstream of other RTKs as it has recently been identified in a cell-based genome-wide RNAi screen for genes required for ERK activation induced by various RTKs, including the Insulin receptor and a homolog of the plateletderived growth factor/vascular endothelial growth factor receptor (Friedman and Perrimon, 2006). A single homolog has been identified in C. elegans, whereas mammals contain at least two related proteins (Douziech et al, 2006;Roignant et al, 2006). Therefore, its function is presumably conserved in other metazoans.…”
Section: Cnk Proteins Are Multidomain-containing Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adult eye phenotypes thus provide a rapid screen for new regulators of the EGFR pathway (Legent et al, 2012;Miura et al, 2008;Roignant et al, 2006;Roignant and Treisman, 2010). Here, we report that a mutation in Vps4 disrupts EGFR signal transduction as well as the transduction of other signaling pathways.…”
Section: Introductionmentioning
confidence: 96%
“…Double-stranded RNAs (dsRNAs) were generated using the MEGAscript T7 and T3 Kits (Ambion) as described previously (Roignant et al, 2006) and 15 µg dsRNA were used to treat 10 6 cells per well for 5 days. EGFR expression was induced for 3 h with 60 µM Cu 2 SO 4 .…”
Section: Cell Culturementioning
confidence: 99%